Slika črne luknje - Vehovar, Jon (Matrika, 2021)
Technological advancements enabled radio astronomers to combine remotely located telescopes to work as one, with a diameter comparable to Earth's. Its resolution was sufficient to support first direct observations of the vicinity of the supermassive black holes at the center of our Milky Way and M87. Produced data enable a unique opportunity for testing Einstein's theory of relativity on scales which haven't been accessible until recently. As predicted by theoretical and numerical modelling, images show a central depression in brightness surrounded by a bright ring which is asymmetric due to the spinning of a black hole around its rotational axis and relativistic beaming of the infalling plasma.
Keywords: astronomija; astronomy; black hole; črne luknje